Chapter Il quadro iniziale - Pazzagli, Rossano (Studi e saggi, 2020)
The present contribution is divided into three sections. The first deals with the features of Italian inner areas and their criticalities; it infers that Community-based cooperatives may well represent a regeneration tool for marginal areas. The second highlights Community-based cooperatives historic development dynamic, starting from the end of 19th century to modern times. The last section discusses the legal aspects of these cooperatives, both in internal relationships among members, and in the relations with external institutions.